Growth, Segregation and Displacement Mechanisms in the Peri-urban of Quito - Gustavo Durán; Marc Martí; Juan Mérida (Íconos)
This paper seeks a qualitative approach to the urban periphery of Quito with the purpose of investigating, in the context of the expansion process of the city, the possible effects of real-estate actions in the socio-spatial transformations of the traditional inhabitants of those areas where the urbanizing process intensified. Through the ethnographic method, sample contextualization techniques, passive observation processes and key actor interviews were used. From identifying the transformations in the urban landscapes and the characterization of the most relevant processes and actors within these transformations, it was possible to build empirical evidence on displacement processes and generation of conflicts as a result of urban development in the periphery in Quito.